OPTIMASI PARAMETER PEMESINAN BUBUT DENGAN VARIASI MEDIA PENDINGIN DAN KECEPATAN SPINDEL TERHADAP KEKASARAN PERMUKAAN BAJA AISI 1045 - Pratama, Aly Wafa; Djumhariyanto, Dwi; Trifiananto, Muhammad; Yudistiro, Danang; Arbiantara, Hari; Ilminafik, Nasrul (STATOR: Jurnal Ilmiah Teknik Mesin, 2023)
The machining process is a process used in the manufacturing industry, the machining process itself has become an important part of the manufacturing industry since the industrial revolution era. In the machining process that is widely used to produce cylindrical products, namely the lathe process. One of the main factors of the quality of processed materials is surface roughness. MQL is a method of providing coolant in the industry which has the function of lowering temperature and reducing friction between the tool and the workpiece. The problem that often occurs in the industrial world, especially manufacturing in the turning process, is the mismatch of the surface roughness of the turning results. Where one of the causes of the roughness results to be inappropriate is the machining parameters that are not adjusted and the high temperature of the workpiece that rubs against the tool during the turning process. Therefore, it is necessary to optimize the machining parameters and coolant used in order to obtain efficient machining parameters and coolant that produces low roughness. The purpose of this study was to determine the effect of variations in the spindle speed parameter and the composition of the coolant mixture, namely clogged oil, dromus and water on the surface roughness value of AISI 1045 steel. From the experiments conducted it was stated that the optimum level of each parameter for surface roughness was level 3 spindle speed 585 rpm and level 3 composition of the coolant mixture 30% clogged oil : 20 dromus : 50% water. The parameter that has a significant effect on the value of surface roughness is the spindle speed.